Dynamic liver scintigraphy: a new way of measuring the function of the reticulo-endothelial system of the liver - Baas, Jens; Senninger, Norbert; Elser, Hubert; Herfarth, Christian (European surgical research, 1995)
The phagocytic function and biokinetics of the hepatic reticuloendothelial system (RES) were evaluated using a 25-nm diameter colloid (NanocollTM) and a scintillation camera technique in opossums with obstruction of the pancreatic duct (group I) and additional obstruction of the common bile duct (group II). The liver net uptake curve was analysed using natural log regression. The regression curves proved to fit very well (r > 0.93) and a parameter R was calculated to describe the curves. In group I there was a slight but significant decrease in the RES function and no morphological change in the pancreas. In group II, RES function was significantly more suppressed than in group I. The opossums developed severe haemorrhagic pancreatitis. The results show that the regression parameter R is well suited to describe liver RES function, and suggest that a suppressed liver RES after biliary obstruction could be an important factor in the pathogenesis of biliary pancreatitis.